Decision Support Systems in Health Care -- Velocity of Apriori Algorithm...EFMI Special Topic Conference, 2017, Israel - SOMEK, Mario; HERCIGONJA-SZEKERES, Mira (Studies in Health Technology & Informatics, 2017)
The amount of stored data in health information systems can reach teraand petabytes and application of specific algorithms in the field of data mining makes finding useful information suitable for making quality business decisions. A frequently used method for determining the rules of the relationship between attributes is the Association rule by applying Apriori algorithm. Lack of basic Apriori algorithm is derived from the slow work due to multiple scanned data sets. By examining the speed of generating the basic rules in relation to the improved Apriori algorithm by using software RapidMiner confirmed that the time required to generate rules for Improved algorithm is shorter, the rules are quickly generated particularly for large data sets, which is an advantage for making decisions.